FAMILY SUPPORT FOR PRISONERS WHILE PASSING THEIR CRIMINAL TERM IN CORRECTIONAL INSTITUTIONS - Maharani, Jesica Triyana; Muhammad, Ali (Universitas Nusa Cendana, 2025)
A person or group of people who commit a criminal act or acts that are contrary to the laws established in a region will certainly receive sanctions or punishment for their actions. Imprisonment is a form of punishment where the crime will rob someone of their freedom and separate them from their environment and family. While convicts are serving their criminal term in prison or detention, especially for first-time offenders, feelings of suffering and disturbance will arise, which arise from the impact of prisonization, which can result in the emergence of mental disorders or pathological mental disorders. One way to help prisoners cope with pressure and adapt to prison life is through family support. Keywords: Prisoners; Family Support; Mental Disorders